THE INFLUENCE OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. KOPENBA JOB SITE ENGINEERING AND MANUFACTURING TANJUNG ENIM - Heriawan, Heriawan; Sari, Novita (Jurnal Manajemen, 2024)
The purpose of this study was to determine and explain how to improve work motivation at PT. Kopenba Job Site Rekayasa Enjiniring and Manufaktur Tanjung Enim. The data analysis method used is quantitative descriptive with SPSS calculations using saturated sample techniques. In analyzing data using the Likert scale, Validity Test, Reliability, Correlation Coefficient, Determination Coefficient, Simple Linear Regression, and Hypothesis Test (t-test). The correlation coefficient result of 83.1% shows a perfect relationship between work motivation and employee performance. Hypothesis (t-test), work motivation is obtained from Tcount> Ttable which is 5.383> 2.306 with a significant value of 0.000 <0.05 then H1 is accepted. This shows that partially the work motivation variable affects employee performance. While the determination coefficient value of 78.8% has a positive and significant effect of work motivation on employee performance at PT. Kopenba Job Site Engineering Engineering and Manufacturing Tanjung Enim This motivation has an important role in improving Employee Performance and the remaining 21.2% is determined by other factors.